Thoracic Trauma Severity score on admission allows to determine the risk of delayed ARDS in trauma patients with pulmonary contusion. Issue 1 (January 2016) - Daurat, Aurélien; Millet, Ingrid; Roustan, Jean-Paul; Maury, Camille; Taourel, Patrice; Jaber, Samir; Capdevila, Xavier; Charbit, Jonathan
Abstract: Background: Pulmonary contusion is a major risk factor of acute respiratory distress syndrome (ARDS) in trauma patients. As this complication may appear after a free interval of 24–48 h, detection of patients at risk is essential. The main objective of this study was to assess the performance of the Thoracic Trauma Severity (TTS) score upon admission in predicting delayed ARDS in blunt trauma patients with pulmonary contusion. Methods: All blunt thoracic trauma patients admitted consecutively to our trauma centre between January 2005 and December 2009 were retrospectively included if they presented a pulmonary contusion on the admission chest computed tomography scan. Main outcome measure was the presence of moderate or severe ARDS (PaO2 /FiO2 ratio ≤ 200) for 48 h or more. The global ability of the TTS score to predict ARDS was studied by ROC curves with a threshold analysis using a grey zone approach. Results: Of 329 patients studied (75% men, mean age 36.9 years [SD 17.8 years], mean Injury Severity Score 21.7 [SD 16.0]), 82 (25%) presented with ARDS (mean lowest PaO2 /FiO2 ratio of 131 [SD 34]). The area under the ROC curves for the TTS score in predicting ARDS was 0.82 (95% CI 0.78–0.86) in the overall population. TTS scores between 8 and 12 belonged to the inconclusive grey zone. A TTS score of 13–25 was found to be independent risk factors of ARDS (OR 25.8 [95% CI 6.7–99.6] P < 0.001). Conclusions: An extreme TTS score on admission accurately predicts the occurrence of delayed ARDS in blunt thoracic trauma patients affected by pulmonary contusion. This simple score could guide early decision making and management for a non-negligible proportion of this specific population.